(untitled) (Research, Society and Development, 2021)
Introduction: Cervical Cancer (CC) is considered a serious public health problem, being the third most common tumor in the female population and the fourth leading cause of death of women from cancer in Brazil. Considering the importance of CC screening, especially in riverside communities, this study aims to present characteristics of cervical cancer screening in riverside populations in the Xingu-Pará region. Methodology: this is a descriptive, cross-sectional study with a quantitative approach, with women living in cities and riverside communities, who sought the health service to perform the preventive examination of the CC. Results: The majority of rural riverside women are brown, with incomplete elementary education, family income below one salary, whereas women living in riverside cities, there is a predominance of brown color with complete secondary education, family income of one minimum wage. Among the risk factors, the early coitarche, multiparity and family history of cervical cancer are registered. Discussion: The socio-economic profile demonstrates that the main characteristics of the women interviewed are predominant in race / brown color, followed by black color and with a low level of education and low family income, and the factors registered as risk factors for illness are more evident in women rural riverside. Conclusion: This study concluded that it is necessary to perform differently among women from the riverside communities. Continuous actions with involvement between health units and the population are necessary, mainly because they are populations with greater difficulty in accessing health services.